SIKAP HKBP TERHADAP OKULTISME DAN EKSORSISME DALAM MASYARAKAT BATAK TOBA: KAJIAN ATAS PRAKTIK OKULTISME DI HKBP NAULI DANOHORBO - Jhon Ferdinand Sihombing; Asigor P. Sitanggang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
The Church's encounter with culture makes it possible for the Church to accept or reject cultures. HKBP Church is one of the tribal churches in Indonesia that accepts and takes care of the Toba Batak tradition. The HKBP Church's acceptance of culture has been accompanied by prohibitions and teachings in the Confession Book and Ruhut Parmahanion Paminsangon (RPP) books. However, there are still congregations that carry out occult practices. This article aims to discuss the current and future manners of the HKBP Church towards occult practices and exorcism in the Toba Batak community. The author will use a qualitative method with literature studies, namely contextualization efforts based on Stephen B. Bevans' theory, especially the synthesis model and based on Richard Niebuhr's views on Christ and Culture, Edgar H. Schein on the cultural structure and Martin Luther on Exorcism. This study finds that the Toba Batak tradition contains positive and negative values. Therefore, this study suggests that the Church needs to conduct a cultural review to find the correct tradition, and the Church must take part in the practice of exorcism.